BEBERAPA CATATAN TENTANG BAHASA PEREMPUAN: PERSPEKTIF WACANA KRITIS - Santoso, Anang (Diksi, 2015)
It is already generally assumed that women possess characteristics distinguishing them from men. One of these characteristics is in their language use. Women's language is considered different from men's. In this context, the term sexist appears. Sexist language represents women and men differently. Such language also represents women's and men's stereotypes, which is sometimes harmful to both sexes but is more often harmful to women only. Understanding women's language involves at least four perspective. First, women's language is perceived as a system of representation, meaning that it is a method of stating or verbalizing a certain event, experience, view, and reality in life. Second, women's language is perceived as a site for social struggle containing a variety of women's ideologies. Third, women's language is perceived as showing women's cornered position. Fourth, women's language is perceived as showing a relation between language and gender where there is asymmetry in language representation between men and women. Keywords : women's language, representation, theory of domination, theory of difference, gender analysis